2009
DOI: 10.1136/thx.2008.110940
|View full text |Cite
|
Sign up to set email alerts
|

Simplified cell culture method for the diagnosis of atypical primary ciliary dyskinesia

Abstract: Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 28 publications
0
28
0
3
Order By: Relevance
“…This may relate to different techniques or equipment, and it is important for each centre to establish their own normal ranges [19]. The diagnosis of PCD was confirmed by tissue culture in all patients with higher than expected nNO levels [16], and so we are confident that the diagnosis is correct. Secondly, it was only possible to study NOS2 and NOS3 mRNA, not protein, so the possibility cannot be excluded that post-translational modification may have affected the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may relate to different techniques or equipment, and it is important for each centre to establish their own normal ranges [19]. The diagnosis of PCD was confirmed by tissue culture in all patients with higher than expected nNO levels [16], and so we are confident that the diagnosis is correct. Secondly, it was only possible to study NOS2 and NOS3 mRNA, not protein, so the possibility cannot be excluded that post-translational modification may have affected the results.…”
Section: Discussionmentioning
confidence: 99%
“…In all subjects, ciliary motion analysis, ultrastructural assessment of cilia on nasal brushings and nNO measurement were performed. nNO measurements, nasal brush biopsy, ciliary motion analysis and ultrastructural studies were performed according to standard methodologies [12][13][14][15][16], detailed in the online supplementary material.…”
Section: Subjectsmentioning
confidence: 99%
“…A diagnosis of PCD was made on the basis of structural and/or functional ciliary abnormalities, as described previously [6][7][8][9][10]. In all subjects, ciliary motion analysis, ultrastructural assessment of cilia, ciliary function after ciliogenesis in culture of nasal brushing samples, and nasal NO measurements were performed when the subject had been free from respiratory infection for o4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Definite diagnosis of PCD was made on the basis of structural and/or functional ciliary abnormalities on both brushing and culture, which take account of both beat frequency and pattern, as previously described [7]. Diagnosis of SCD was made when PCD was excluded and ciliary abnormalities were considered as acquired.…”
Section: Subjectsmentioning
confidence: 99%
“…In the past, culture was mainly performed on cells obtained by nasal forceps biopsy [6], which is painful. Recently, we have demonstrated that cell culture is possible directly from the brushed nasal epithelial cells, thus reducing the need for a second and more traumatic sampling [7]. With our simplified culture system, the evaluation of ciliary activity is only possible on the 21st day of suspension culture, when new cilia formation has definitely occurred.…”
mentioning
confidence: 99%